2012
DOI: 10.1371/journal.ppat.1002494
|View full text |Cite
|
Sign up to set email alerts
|

Development of Functional and Molecular Correlates of Vaccine-Induced Protection for a Model Intracellular Pathogen, F. tularensis LVS

Abstract: In contrast with common human infections for which vaccine efficacy can be evaluated directly in field studies, alternative strategies are needed to evaluate efficacy for slowly developing or sporadic diseases like tularemia. For diseases such as these caused by intracellular bacteria, serological measures of antibodies are generally not predictive. Here, we used vaccines varying in efficacy to explore development of clinically useful correlates of protection for intracellular bacteria, using Francisella tular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
117
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(133 citation statements)
references
References 72 publications
10
117
0
3
Order By: Relevance
“…Importantly, we found that immunization with LVS-VϩMPL increased cellular immunity as well; not only did it increase the number of IFN-␥-producing T cells and the level of secreted IFN-␥, but it also enhanced the ability of splenic T cells from LVS-VϩMPL-immunized mice to activate macrophages in vitro to kill or inhibit the intracellular replication of F. tularensis. The assay using splenocytes to control intramacrophage growth of F. tularensis has been shown by others to represent an excellent correlate of cell-mediated immunity (35).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Importantly, we found that immunization with LVS-VϩMPL increased cellular immunity as well; not only did it increase the number of IFN-␥-producing T cells and the level of secreted IFN-␥, but it also enhanced the ability of splenic T cells from LVS-VϩMPL-immunized mice to activate macrophages in vitro to kill or inhibit the intracellular replication of F. tularensis. The assay using splenocytes to control intramacrophage growth of F. tularensis has been shown by others to represent an excellent correlate of cell-mediated immunity (35).…”
Section: Discussionmentioning
confidence: 99%
“…Functional assays utilizing coculture of F. tularensis infected BMDM and splenocytes from immunized mice were performed as previously described (35,38). Briefly, bone marrow was harvested from immunologically naive mice and cultured for 1 week in Dulbecco's modified Eagle's medium (DMEM) supplemented with 10% conditioned medium from the LADMAC cell line as a source of macrophage colony-stimulating factor (M-CSF), as well as 10% fetal bovine serum (FBS) (Atlanta Biologicals, Flowery Branch, GA), 200 mM L-glutamine (Gibco, Grand Island, NY), and 10 mM HEPES buffer (Sigma).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Single-cell suspensions prepared from spleens or lungs were stained for a panel of murine cell surface markers and analyzed using a Becton, Dickinson LSR II flow cytometer (San Jose, CA) and FlowJo software (Tree Star, Inc.), as previously described (3). Briefly, cells were washed and resuspended in PBS-2% FCS.…”
Section: Mice Male C57bl/6j Mice and B6129s6-tbx21mentioning
confidence: 99%